2013
DOI: 10.1589/jpts.25.51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3 Weeks of Balneotherapy on Immunological Parameters, Trace Metal Elements and Mood States in Pilots

Abstract: Abstract.[Purpose] The aim of this study was to investigate the effects of balneotherapy on immunological parameters, trace metal elements and mood states in pilots.[Subjects] Thirty-six healthy male pilots were enrolled into this study.[Methods] All subjects received therapy for 3 weeks. They took entire-body immersion baths in thermomineral water for 30 min a day for 3 weeks. Blood samples were taken 1 day before and after the balneotherapy treatment. Blood concentrations of trace metal elements were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…21,38 Xu et al also concluded that balneotherapy with mineral water provided psychological benefits, such as improved relaxation and relief from sleep disorders and chronic pain disorders, in pilots with mood states. 20 Liao found that insomnia in the elderly is associated with changes in circadian body temperature rhythms, and in this sense, the manipulation of body temperature before sleep onset may improve sleep quality in the elderly. For example, a hot bath in the afternoon aids night-time sleep for healthy elderly subjects with insomnia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…21,38 Xu et al also concluded that balneotherapy with mineral water provided psychological benefits, such as improved relaxation and relief from sleep disorders and chronic pain disorders, in pilots with mood states. 20 Liao found that insomnia in the elderly is associated with changes in circadian body temperature rhythms, and in this sense, the manipulation of body temperature before sleep onset may improve sleep quality in the elderly. For example, a hot bath in the afternoon aids night-time sleep for healthy elderly subjects with insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated the effect of balneotherapy in localized pain reduction and improved quality of life related to health, and Xu et al . concluded that these benefits play important roles in the improvement of mood states after treatment with balneotherapy . Gonzalez et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Venier, Larese, and Filon's studies show that metallic ions can easily permeate the skin (nickel, cobalt, and chromium) [ 33 ]. Human skin is permeable to Mg, Ca, K, Cu, Br, Rb, Ca, Fe, Pb, Cd, and Zn ions [ 34 – 37 ] and sulfates and nitrate anions [ 35 ]. Factors influencing percutaneous absorption through the skin include (1) physicochemical properties of the test compound, (2) skin properties and metabolism, (3) dose and volume of test substance, and (4) duration of exposure [ 38 ].…”
Section: Introductionmentioning
confidence: 99%